2007
DOI: 10.1007/s00420-006-0167-7
|View full text |Cite
|
Sign up to set email alerts
|

Airflow limitation among workers in a labour-intensive coal mine in Tanzania

Abstract: Exposure to respirable coal mine dust was associated with airway limitation as measured by FEV(1)/FVC and predicted FEV(1)%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
2
4
0
1
Order By: Relevance
“…al. also reported that exposure to coal mine dust was associated with airway limitation as measured by FEV 1 /FVC and the predicted FEV 1 (%) [29]. By comparing the three groups of miners in the present study, our lung ventilation function data provide further evidence that airway dysfunction may be a predominant feature in the initial development and progression of the lung disease associated with coal mining.…”
Section: Discussionsupporting
confidence: 71%
“…al. also reported that exposure to coal mine dust was associated with airway limitation as measured by FEV 1 /FVC and the predicted FEV 1 (%) [29]. By comparing the three groups of miners in the present study, our lung ventilation function data provide further evidence that airway dysfunction may be a predominant feature in the initial development and progression of the lung disease associated with coal mining.…”
Section: Discussionsupporting
confidence: 71%
“…Our data showed that the majority of CWP patients were tunneling and coal mining workers. In general, tunneling and mining miners had highest levels of dust exposure and the highest risk for CWP [ 13 , 14 ]. The highest numbers of patients with the higher stages corresponded to the tunneling and mining miners.…”
Section: Discussionmentioning
confidence: 99%
“…For current smokers, the amount of cigarette packets smoked in a year was calculated by multiplying numbers of cigarettes smoked per day times duration of smoking in days divided by 20. Never smokers were defined as individuals who had never smoked [14]. Questions on other pulmonary diseases which might have confounded the results were elicited.…”
Section: Respiratory Health Questionnairementioning
confidence: 99%